ROLE OF MODIFIED EARLY WARNING SCORE IN EVALUATING MORTALITY IN POSTOPERATIVE PERIOD - Nivedita; K, Mohammed Faizulviqhas; Alam, Mohammad Noor (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The intent of the study is to analyze the role of modified early warning score (MEWS) in the assessment of the need of early intervention and surgical intensive care unit (SICU) admission in patients undergoing elective and emergency major surgical procedures. Methods: This prospective study incorporated 150 patients who underwent emergency or elective major surgical procedures, with monitoring of physiological parameters in the post-operative period with implementation of MEWS. The MEWS score of 1–3: Escalation of monitoring done. MEWS of 4–5: Escalation of monitoring, urgent assessment by the surgical team, shift of patient to intensive care unit (ICU) if required. MEWS of ≥6: Shift of patient to ICU with emergency assessment by the surgical/medical/ICU team. Outcomes were (1) improvement in patients’ clinical condition after early goal-directed therapies (frequent monitoring, shifting to ICU), (2) discharged alive from the hospital, and (3) patient death. Results: In our study, all the patients with MEWS from 1 to 7 were discharged alive and all the patients with a score above ≥8 were succumbed to death suggesting MEWS score of ≥8 implicates the strict need for SICU admission and an increased mortality of the patient in the post-operative period. MEWS improved communication between nursing staff, junior doctors with surgical team to “flag-up” and prioritize patients. Conclusion: The MEWS is an important risk management tool that is simple to implement and effective in identifying the early deterioration of the patients, which can be used as a routine protocol in post-operative period and assessing the need of ICU for further interventions.